Uma aula na cabeça, uma câmera na mão: a transposição para videoaula na formação de professores na perspectiva da complexidade - Priuli, Ricardo Medeiros (2017)
The present research aims at describing and interpreting a phenomenon of human experience understood as the process of transposition according to the conception of Field (2001), that is, an adaptation of the lesson for educational video from the perspective of the language teachers in formation. The focus of this study was experienced in the context of an extension course developed at a private university located in the eastern zone of São Paulo, targeting students from the first semester of the Language and Literature course. The course has as central theme the audiovisual language as an essential element for the technological and multilearning training of language teachers who are still undergraduate students. Audiovisual language is increasingly emerging in the education universe, mainly in the production of digital materials and resources for hybrid contexts and online teaching. Thus, it becomes relevant to study how the processes of transposition of the lesson to the educational video occur in the perspective of teacher-students of Letters who can act in new teaching scenarios and who need to have a qualification that will instrumentalize them to act in a empowered way Having as an interpretive material the textual record of the experiences lived in the course, this research was drawn from a qualitative research approach in the context of Applied Linguistics, denominated as Complex Hermeneutic-Phenomenological Approach (Freire 2010,2012,2017) that allows understand the phenomena of human experience from the textualization and routines of text interpretation. Based on the theoretical references of the area of complexity (Morin 2014a, 2015), and of audiovisual language, cinema, screenplay and pedagogy of the audiovisual (Wohlgemuth 2005), the findings allow reflections and discussions about the technological formation of teachers as autonomous subjects in the educational process in new teaching and teaching scenarios as suggested by Libâneo (2011), so that not only does it present an evident deficiency in the curriculum, but also possibility of technological qualification in face of the new challenges of teaching in the current scenarios of the educational universe that demand new knowledge